RETRACTED: Perkembangan dan Kontroversi Mengenai Eksistensi Multiverse - Romli, Sunaryo; Muslim, Muslim; Suhandi, Andi (Program Studi Pendidikan IPA, FKIP Universitas Pancasakti (UPS) Tegal, 2023)
RETRACTED After careful consideration and thorough review of the article published in the PSEJ (Pancasakti Science Education Journal) entitled